PEMBUATAN KUIS PADA MULTIMEDIA PEMBELAJARAN INTERAKTIRF DENGAN FITUR TRIGGERSSOFTWAREPOWERPOINT - Ardian Arief (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Â Abstract: At this time the learning media is one aspect that plays a role in learning. One is the role of media in the form of interactive learning, where students become the center of learning and the teacher as a facilitator and motivator. One aspect that needs to appear on an interactive learning media is the quiz feature. Microsoft Powerpoint is one of the bases that can be used for developing interactive learning media. Through this application the presentation of the evaluation of learning can be realized with interesting, fun, and attract students to focus in evaluation of learning. Techniques or features that can be used are triggers and script macros.